Diabetes mellitus, glucose control parameters and platelet reactivity in ticagrelor treated patients. Issue 143 (July 2016) - Nardin, Matteo; Verdoia, Monica; Sartori, Chiara; Pergolini, Patrizia; Rolla, Roberta; Barbieri, Lucia; Schaffer, Alon; Bellomo, Giorgio; Suryapranata, Harry; De Luca, Giuseppe; ,
Abstract: Introduction: Despite the recent advances, prognostic difference between diabetic and non diabetic patients is still marked after an acute coronary syndrome. Diabetes mellitus and poor glycemic control represent well established pro-thrombotic conditions, as inadequate glycemic control can lead to impaired responsiveness to antiplatelet therapies. Among new antiplatelet agents, ticagrelor has provided more potent platelet inhibition, potentially offering benefits in reducing residual high-on treatment platelet reactivity. However, no study has so far investigated the relationship between diabetes mellitus and platelet reactivity in patients treated with ticagrelor after an acute coronary syndrome (ACS). Methods: In patients treated with acetylsalicylic acid (100–160 mg) and ticagrelor (90 mg twice a day) platelet reactivity was assessed at 30–90 days post-discharge for an ACS. Diabetic status was defined before discharge. Multiple-electrode aggregometry was used to assess platelet function. High residual platelet reactivity was defined as ADP-test results > 417 AU ∗ min. Results: Diabetes was observed in 86 out of 224 patients (38.4%). Diabetes was significantly associated with older age, higher BMI, renal failure, hypertension, treatment with diuretics, higher levels of WBC, glycaemia, HbA1c, and lower levels of HDL-cholesterol. Platelet reactivity was higher in diabetic patients as compared to non-diabetic ones for all the different activating stimuli tested. A total of 29 patients (12.9%) displayed high-residual platelet reactivity with ticagrelor with an almost double rate in diabetics as compared to non-diabetics (18.8% vs 9.4%, p  = 0.06; adjusted OR[95%CI] = 2.12[1.1–4.1], p  = 0.025). A progressive increase of platelet reactivity was observed for higher HbA1c levels ( r  = 0.15, p  = 0.029). Conclusion: The present study shows that diabetic patients display higher platelet reactivity despite dual antiplatelet therapy. In fact, diabetes mellitus emerged as independent predictor of high-residual platelet reactivity in post-ACS patients treated with ticagrelor. Graphical abstract: